PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI DI PG.TJOEKIR, JOMBANG - SUSILO PRADANA, HENDRA (Jurnal Ilmu Manajemen (JIM), 2016)
The purpose of this research was to analyze the effect of partial training and work motivation on employee productivity at the department of production in PG. Tjoekir, Jombang and simultaneous effect of training and work motivation on employee productivity production at PG. Tjoekir, Jombang. This research uses a quantitative approach, the variables were training (X1), work motivation (X2) and employee productivity (Y). With the number of population in this research as many as 132 employees of the production department of PG. Tjoekir, Jombang. The sample size set out of 79 employees in the production department of PG. Tjoekir, Jombang. Multiple linear regression analysis of generated regression equation Y = 2,381 + 0.297 X1 + 0.147 X2. The F-test resulted in the significant value of 0.030 <0.05. While the t test significance value generating X1 as 0,011 < 0,05 and X2 as 0,0385 > 0,05. Keywords: training, motivation, productivity